Дослідження впливу хорового співу на формування національної свідомості - Мартинюк Анатолій; Martynyuk Anatoliy; Мартинюк Тетяна; Martynyuk Tetyana; Бочаріна Наталія; Bocharina Natalia (Видавництво «Код», 2025)
Резюме. У статті представлено методологічне підґрунтя, вибірку та процедуру емпіричного дослідження формування національної свідомості в осіб студентського віку, які займаються хоровим співом. Дослідження ґрунтується на міждисциплінарному підході, що об’єднує концепції системної, особистісно орієнтованої, гуманістичної та вікової психології. Обґрунтовано доцільність застосування комплексного підходу, що дозволяє отримати глибоке розуміння прояву формування компонентів національної самосвідомості особистості в контексті хорового співу.

Abstract. The article presents the methodological basis, sample and procedure of empirical research on the formation of national consciousness in students engaged in choral singing. The study is based on an interdisciplinary approach that combines the concepts of systemic, personality-oriented, humanistic and age psychology. A sample of 56 participants aged 20 to 25 is described, four stages of the research procedure are identified: piloting, questionnaires, basic research and data processing. The psychodiagnostic research toolkit is presented, which includes quantitative (tests) and qualitative (interviews, diaries, observations) methods. The feasibility of using a comprehensive approach is substantiated, which allows for a deep understanding of the manifestation of the formation of the components of a person’s national self-consciousness in the context of choral singing. The role of choral singing as a mediator of the development of a person’s self-consciousness is determined. The results of the conducted experimental study confirm the hypothesis of the positive impact of choral singing on the formation of national self-awareness of a young person. Students' participation in choral activities with a nationally oriented repertoire contributed to the activation of key psychological mechanisms, in particular emotional identification, cognitive comprehension of national values, and social inclusion in the ethnocultural space. The experimental group recorded significantly higher rates of ethnic affiliation, emotional inclusion, civic activity, and positive attitude towards national symbols, language, and traditions, compared to the control group.
Research on the influence of choral singing on the formation of national consciousness
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: національна самосвідомість; хоровий спів; рівні формування національної самосвідомості; когнітивний компонент національної самосвідомості; поведінковий компонент національної самосвідомості